PENGGOLONGAN 23 JENIS ROTAN INDONESIA BERDASARKAN KERAPATAN DAN KUAT TARIK SEJAJAR SERAT - Abdurachman; Jasni; Rohmah Pari; Esti Rini Satiti (BRIN Publishing, 2017)
Rattan utilization is mainly determined by its physical and mechanical characteristics of density and tensile strength, where the higher the physical and mechanical properties, the better quality of the cane. In South East Asia region including Indonesia, two of eight genera, Calamus and Daemonorops are classified into high economic value, however the physical and mechanical characteristic of lesser known rattan species has not been studied intensively. This paper classifies 23 of lesser known rattan species into four classes based on its density and tensile strength parallel to grain. Density was measured based on gravimetric method and tensile strength parallel to grain was tested using Universal Testing Machine (UTM). Results show that in term of physical and mechanical properties, one species belongs to class I (very good), twelve species are classified into class II(good) and III (moderate). Ten rattan species are grouped into class IV (poor). Among 23 rattan species, highly recommended commercial rattan species are Calamus holttumii Furt., Calamus nematospadix Becc., and Korthalsia celebica Becc. While, Calamus sp., Korthalsia rostrata Blume and Daemonorops sabut Becc are less recommended.